XyloDensMap: a georeferenced dataset for the wood density of 110,000 trees from 156 European species in France - Henri Cuny; Jean-Michel Leban; Jean-Christophe Hervé; Jean-Daniel Bontemps; Baptiste Kerfriden; Philippe Jacquin; Maxime Lacarin; Vincent Dauffy; Cédric Duprez; Stéphanie Wurpillot (Scientific Data)
Abstract The XyloDensMap dataset aims to provide comprehensive quantification of wood density and its variation across European tree species and their populations. Data were obtained by combining spatially systematic sampling of the French National Forest Inventory (NFI), and an original high-flow method of wood density measurement by X-ray Computed Tomography. Wood density was measured on 110,763 wood cores sampled at breast height over the period 2016–2019 on 20,697 NFI plots evenly distributed across mainland France. The dataset covers 156 European tree species and wide gradients of elevations (from 0 to 2,300 m above sea level), climates (oceanic, continental, mountain and Mediterranean climates) and soil conditions. It encompasses most European forest types, with the exception of boreal forests. The number of wood density measurements is roughly proportional to the abundance of tree species in the forest area sampled. This dataset’s potential extends to the intensive documentation of a major ecological trait, the assessment of the drivers of wood density variation, or the improvement of forest biomass and carbon estimates, and their uncertainty.